Effect of Affirmative Actions on Student Permanence at a Brazilian Federal University - Lusia Ribeiro Ferreira; Anderson Betti Frare; Débora Gomes de Gomes; Flávia Regina Czarneski; Márcia Bianchi (Revista Facultad de Ciencias Económicas)
The study aims to identify the Affirmative Actions (AAS) promoted among students of business programs at a Brazilian federal university and analyze whether, in the students’ opinion, they meet the fundamental assumptions of the theory of justice. The documentary survey of AA examines student housing, financial aid for student parents, food, transport, permanence, and pedagogical support. Sixty-two respondents took part in the survey. The results show that personal factors, especially those of a psychological nature, adversely affect the permanence and performance of university students. Considering the students’ perception of Rawl’s “equal liberty” and equality of opportunity, the university’s AAS are understood to reflect the assumptions of John Rawls’ theory of justice.